Pengaruh Explosive Power Otot Tungkai Dengan Hasil Lompat Jauh Gaya Jongkok Siswa Kelas X Ips Sma Muhammadiyah Kabupaten Kampar - Muhammad Fikri (Inspiree)
Based on the observations made by the author in Class X Social Studies at SMA Muhammadiyah Kampar Regency, it was found that the ability of students to do long jumps was still in the below-average category. This is due to the low physical condition of students so that they do not produce maximum explosive power of the leg muscles. This research was conducted using a correlational research design. Based on the results of research that has been carried out on class X students of SMA Muhammadiyah Kampar Regency, the value of count = 0.811 > table = 0.514. Obtained r = 0.811 including very strong category. Significance test using the t-test Significance formula. From the calculation results, it is known that t count = 5,006 while t table = 1,771. So t count = 5,006 > t table = 1,771. Thus, a conclusion can be drawn that: There is an effect of explosive power in the leg muscles with the results of the long jump squatting style for X grade students of SMA Muhammadiyah Kampar Regency.